"Pnicogen bonds" or "chalcogen bonds": exploiting the effect of substitution on the formation of P⋯Se noncovalent bonds. Issue 20 (5th May 2016) - Shukla, Rahul; Chopra, Deepak
Abstract : A direct comparison of pnicogen bonds and chalcogen bonds in P⋯Se non-covalent interactions. Abstract : In this article, we have analyzed the nature and characteristics of P⋯Se noncovalent interactions by studying the effect of substitution on XH2 P⋯SeH2, H3 P⋯SeHX and XH2 P⋯SeHX (X= –H, –F, –CH3, –CF3, –Cl, –OH, –OCH3, –NH2, –NHCH3, and –CN) as our systems of interest at MP2/aug-cc-pVDZ level of theory. Binding energy calculations depict that binding energy increases in the order XH2 P⋯SeH2 < H3 P⋯SeHX < XH2 P⋯SeHX with the nature of the substituent having a direct effect on the strength of the interactions. P⋯Se contacts as short as 2.52 Å were observed and analyzed in our study. The energy values for P⋯Se contacts were found to exist in the range of −1.20 kcal mol −1 to −7.89 kcal mol −1 . The topological analysis confirms the presence of P⋯Se contacts in all the complexes with characteristics similar to hydrogen bonds. NBO analysis helped in categorizing these interactions into pnicogen and chalcogen bonds, depending on the strength of P(lp) to σ *(Se–X) orbitals or Se(lp) to σ*(P–X) orbitals.